Perceived Risk of Weekly Marijuana Use Among Students Participating in the National Survey on Drug Use and Health - Dunn, Michael S. (Journal of drug issues, 2025)
This study sought to assess the relationship of risk perception of weekly marijuana use and the influence of parental, peer, and school factors as predictors among U.S. adolescents. Data for this study was derived from the 2020 National Survey on Drug Use and Health. Students who reported strong parental involvement/support, peer disapproval of marijuana use, low perception of peer use, and enjoyed school were more likely to report that using marijuana weekly was a risk behavior. Students who reported no lifetime alcohol or illicit drug use were more likely to view weekly marijuana use as a risk behavior. Differences were also observed for sex of respondent. This study further adds evidence of the influence of parental, peer, and school factors as effective strategies to control adolescent marijuana use. There is a need for multidimensional programs that target adolescents’ perceptions of risk of marijuana use, as well as targeting significant others.